Theoretical Aspects Of The Nature And Influencing Factors Of Eco-Innovations - Auzina, Anita; Zvirbule, Andra; Tihonova, Karina (European Scientific Journal, ESJ, 2017)
The world faces such serious environmental problems as climate change, the exhaustion of natural resources and the loss of biodiversity, which create self-destruction threats to our mankind. This situation has become so real and visible that it caused response in the form of ecoinnovations. Eco-innovations are any kind of innovation that contribute to more efficient exploitation of resources or environmental protection. Ecoinnovations involve the sustainable exploitation of natural resources, ensure increase in the quality of life, meet today’s needs without compromising the ability of future generations to meet their own needs and contribute to the preservation of biodiversity for an unlimited period. Eco-innovations involve not only environmental gains but also provide an opportunity for entrepreneurship. Eco-innovations reduce the expenses of enterprises, help the enterprises to use new opportunities for their growth and strengthen the image of the enterprises among the public. The eco-innovation initiative was launched in 2008, and it was part of several European Union (EU) innovation programmes. For this reason, the research problem and the research aim were determined by the necessity to identify and examine the theoretical aspects of the nature and kinds of this relatively new initiative, which are further used as a basis for empirical research. The research aim is to characterise and examine the theoretical aspects of the nature and influencing factors of eco-innovations. The research employed general analysis methods, logical construction, and quantitative methods: monographic, content analysis for the specific literature and research papers, a specific case study and graphical methods for data analysis and depiction.